2017
DOI: 10.1111/jvh.12795
|View full text |Cite
|
Sign up to set email alerts
|

Resistance characterization of ledipasvir and velpatasvir in hepatitis C virus genotype 4

Abstract: HCV genotype 4 (GT4) has often been overlooked in drug development, even though it infects ~20 million people worldwide. Ledipasvir/sofosbuvir and sofosbuvir/velpatasvir were highly efficacious in GT4 HCV-infected patients from GS-US-337-1119 and GS-US-342-1138. Here, we characterize the resistance profile of ledipasvir (LDV) and velpatasvir (VEL) in patients with GT4 HCV infection. NS5A deep-sequencing was performed for 454 patients infected with HCV GT4 at baseline, including 44 patients enrolled in GS-US-33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 24 publications
2
32
1
Order By: Relevance
“…High SVR12 rates of 96.2% or 95.4% were reported in HCV GT4‐infected patients treated with either OBV/PTV/r (n = 122) or SOF/LDV (n = 130), respectively, with or without RBV in a real‐world setting, but an analysis of the prevalence of NS5A baseline polymorphisms was not included in the study results . Another study reported SVR12 rates of 93% (41/44) in GT4‐infected patients treated with SOF/LDV, which included 25 patients with baseline polymorphisms L28M and/or L30R/S in NS5A; all 3 virologic failures had L28M/V with or without L30R in NS5A at baseline, which corresponds with a 37‐ to 67‐fold change in LDV activity against L28M/V and L30R in GT4 . In our combined cohort analysis, SVR12 rates of 98.9% (94/95) were observed for HCV GT4‐infected patients with an NS5A polymorphism at baseline treated with OBV/PTV/r plus RBV in the PEARL‐I and AGATE‐I studies, indicating that there was no impact of NS5A baseline polymorphisms on treatment outcome, even though 35.8% (95/265, excluding the common T/P58 polymorphism in GT4d) of the patient sequences had an NS5A polymorphism at a resistance‐associated amino acid position; this included 78 patients with L28M and/or L30R/S in NS5A (not counting subtype 4d where R30 is wild‐type).…”
Section: Discussionmentioning
confidence: 99%
“…High SVR12 rates of 96.2% or 95.4% were reported in HCV GT4‐infected patients treated with either OBV/PTV/r (n = 122) or SOF/LDV (n = 130), respectively, with or without RBV in a real‐world setting, but an analysis of the prevalence of NS5A baseline polymorphisms was not included in the study results . Another study reported SVR12 rates of 93% (41/44) in GT4‐infected patients treated with SOF/LDV, which included 25 patients with baseline polymorphisms L28M and/or L30R/S in NS5A; all 3 virologic failures had L28M/V with or without L30R in NS5A at baseline, which corresponds with a 37‐ to 67‐fold change in LDV activity against L28M/V and L30R in GT4 . In our combined cohort analysis, SVR12 rates of 98.9% (94/95) were observed for HCV GT4‐infected patients with an NS5A polymorphism at baseline treated with OBV/PTV/r plus RBV in the PEARL‐I and AGATE‐I studies, indicating that there was no impact of NS5A baseline polymorphisms on treatment outcome, even though 35.8% (95/265, excluding the common T/P58 polymorphism in GT4d) of the patient sequences had an NS5A polymorphism at a resistance‐associated amino acid position; this included 78 patients with L28M and/or L30R/S in NS5A (not counting subtype 4d where R30 is wild‐type).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, HCV RNA was extracted with the QIASymphony DSP Virus/Pathogen kit on a QIASymphony device (Qiagen GmbH, Hilden, Germany), according to the manufacturer's instructions. Complementary DNA synthesis was performed with the OneStep RT‐PCR kit (Qiagen GmbH) with sets of primers adapted to the viral regions targeted . Nested PCR was then performed with common primers and, when necessary, genotype‐specific primers.…”
Section: Methodsmentioning
confidence: 99%
“…In the pooled PEARL‐I and AGATE‐I studies, clinical trials including patients treated with ombitasvir/paritaprevir/ritonavir, only 1 of 101 French genotype 4–infected patients was infected with subtype 4r . In the pooled GS‐US‐337‐1119 and ASTRAL‐1 trials, which included patients from Europe and the United States treated with sofosbuvir/ledipasvir and sofosbuvir/velpatasvir, respectively, 5 of 160 genotype 4–infected patients (i.e., 3.1%) were infected with subtype 4r …”
mentioning
confidence: 99%
“…Extensive HCV genetic variability exists at multiple key NS5A resistance‐associated amino acid positions, both across and within different HCV subtypes . Recent studies have shown that reduced susceptibility to ledipasvir for some GT 4b and 4r isolates is associated with the presence of NS5A resistance‐associated substitutions, which may explain occurrences of ledipasvir/sofosbuvir virologic failure among patients with these subtypes . Nevertheless, more data are needed with various NS5A inhibitor‐containing regimens before we can draw firm conclusions about the impact of NS5A genetic variability on treatment outcomes for patients with GT 4b, 4r and other less common subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture studies demonstrated antiviral activity of each drug component against each approved GT, with data generally demonstrating consistent activity across several representative subtypes of GT 4 and 6. Although it is not feasible to capture all of the genetic diversity of GT 4 and 6 subtypes in cell culture studies and clinical trials, antiviral activity generally has been demonstrated, at minimum, across the most common representative subtypes of GT 4 and 6…”
Section: Introductionmentioning
confidence: 99%